Comparative analysis of web development frameworks in PHP: Codeigniter, Cakephp and Yii - Rak, Karol; Dzieńkowski, Mariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
This study presents a comparative analysis of three PHP frameworks: CodeIgniter, Yii, and CakePHP, focusing on performance, reliability, resource efficiency, stability, and community support. Three identical applications performing CRUD (Create, Read, Update, Delete) operations on a database were developed for testing. The evaluation metrics included request handling speed, CPU and memory usage, error rates under varying workloads (10 to 16,000 virtual users), and framework popularity within the developer community. Experiments were conducted using Apache JMeter and PerfMon in a controlled testing environment. The results indicate that CodeIgniter outperformed Yii and CakePHP in most scenarios, demonstrating the lowest memory consumption, fastest response times, and greater stability under high concurrency. Its lack of an ORM (Object-Relational Mapping), replaced by a procedural QueryBuilder, contributed to this performance advantage. By contrast, Yii and CakePHP, which rely on ORM, required more resources and showed greater CPU instability, particularly under heavy load.